Diagnosing the voids of knowledge in the transformation process in managing and standardizing smart city development: the case of the government of Indonesia - Panjaitan, Jenri M. P.; Bastian, Indra; Unggara, Ilham; Susanto, Efa Agus; Sumiyana, Sumiyana (Frontiers in Sustainable Cities, 2023)
Purpose: This research investigates smart city development projects implemented by the Government of Indonesia (GoI) since 2017 at the regional and municipal levels. Moreover, it provides a critical perspective on the lack of knowledge of the transformation process, substance knowledge, and the wide-regime shifting balance of required knowledge to accomplish smart city development. From the project scope perspective, this research elaborates on technical defaults of the regional and municipal GoI’s initiating, doing, and implementing smart cities. Research Methodology: The authors develop semi-structured interviews to explore how these project doers operate in each stage of the smart city development, including initiation, work in progress, implementation and reporting. In addition, the research questions of this semi-structured interview are derived from this study’s critical perspective and the knowledge domains of smart city development. Originality: First, this study sheds light on the development of 100 smart cities by the GoI, financing 50 projects since 2017 that have not yet become finished products, indicating design failure. Second, we argue that the blueprint designed by the GoI smart communities does not demonstrate comprehensive political will or the conducting of socio-cultural and technical analyses to encourage and support the development of smart cities. Third, this study uniquely highlights that the GoI wants to build smart cities in collective cognition or mutual understanding, which lacks knowledge of the transformation process and substance knowledge for system analysis and design, development, and implementation, leading to uncertainty and diverse approaches in smart city development across various regions and municipalities. Fourth, it criticises the misalignment and imbalance of knowledge between the GoI, the targeted regions and municipals, and all agents involved in developing smart cities. Findings: The authors find four unique theme formulations: the GoI’s behaviours in equivalencing with regular procurement, the voids of the knowledge of the transformation process, substance knowledge boundaries, letting these projects progress without accompanying committed knowledge boundaries and working for a future without a signifier. Finally, this study suggests that the government should prioritise mastery of knowledge of the transformation processes in smart city development and implement agile strategies to ensure these projects’ success and future benefits.